PENENTUAN KARAKTERISTIK ENDAPAN MINERAL LOGAM BERDASARKAN DATA INDUCED POLARIZATION (IP) PADA DAERAH PROSPEK CBL, BANTEN - Trianto, Wahyu - (Physics Student Journal, 2014)
Â A research has been done in IUP exploration area of PT. Antam in Pandeglang, Banten. The method used was Time Domain Induced Polarization (TDIP) Dipole-pole Configuration Geoelectricity. The objective of this research was to identify the existence of metal mineral underground based on the rock resistivity and chargeability values. The TDIP data were taken on four tracks of 5 km long and 25 cm long interelectrode spaces. The results of TDIP method were true resistivity and chargeability of each track. The existence of the metal mineral in the research area based on the resistivity data was on the low zone (< 580 Ohm.m), while the existence of the metal mineral based on the chargeability data was on the high zone (> 80 ms) with northwest-southeast distributing pattern. Key words : Metal mineral, Geoelectricity, Time Domain of Induced Polarization Â